Microwave enhanced synthesis of chitosan-graft-polyacrylamide molecularly imprinted polymer (MIP) for selective extraction of antioxidants - Saifuddin N.; Yasumira A.A.N. (Hindawi Limited, 2023)
Polymers have been molecularly imprinted for the purpose of binding specifically to ?-tocotrienol (vitamin E). A molecularly imprinted polymer (MIP) material was prepared using ?-tocotrienol as the imprinted molecule, acrylamide as functional monomer and macroporous chitosan beads as functional matrix. Chitosan-graft-polyacrylamide was synthesized without any radical initiator or catalyst using microwave (MW) irradiation. The representative microwave synthesized graft copolymer was characterized by fourier transform-infrared spectroscopy, taking chitosan as a reference. Microwave irradiation was exploited for polyacrylamide grafting on the cross-linked chitosan beads to produce MIP, where both time as well as chemicals can be saved. It can be assumed that the chitosan coated polyacrylamide MIP will have better pH stability and enhanced adsorption capacity. The maximum adsorption capacity was observed to be 3.95 mg/g of MIP, which gave removal efficiency of 93%. After 4 h, the change of adsorption capacities for ?-tocotrienol did not show notable effects. The Langmuir and Freundlich adsorption models were also applied to describe the equilibrium isotherms.